CAN AMBULANCE DATA BE USED TO REDUCE COMMUNITY VIOLENCE? EXPLORATORY RECORD LINKAGE STUDY. Issue 10 (7th September 2013) - Boyle, A; Ariel, B; Weinborn, C
Abstract : Objectives & Background: Emergency Department information sharing with Community Safety Partnerships and the Police is well established, Emergency Department Data about the location, time of assault and weapon type is shared with the police to support targetted policing and licensing decisions. It is not established whether ambulance data, which routinely collects automated location and time data, provides additional information to police and emergency department data. We aimed to find out what proportion of ambulance call outs to assault was not recorded by the police or the emergency department services. Methods: We compared routine, anonymous aggregate data from the police and ambulance service about calls for service to violent crime in Peterborough, England in 2011–2012. We used two methods of identifying matches. The first is 'hotspotting' which uses spatio-temporal methods to identify clusters. The second is by manually matching individual cases in time and location. Results: 775 calls for service were made to the ambulance service to victims of assault. 347 (49%) of these cases were transported to hospital. 3, 997 calls for police service to victims of violence were made in the same time period. The demographic and temporal characteristics of the two lists were similar. Between 125 and 204 cases could be matched, depending on case definition. Conclusion: The ambulance service is responding to many victims of community violence that are not recorded by the police and probably not recorded by the emergency department. Ambulance data has potential to inform licensing and targetted policing. It is not proven whether this will reduce community violence.